Psychological assessment and biofeedback mitigation of tension-type headaches in children - Pop-Jordanova, N; Zorcec, T (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2009)
The research concerned a group of 59 children, 22 girls and 37 boys, mean age 12.5 +/- 1.24 years, with tension type headaches. Their clinical results (neurological, neuropsychological, radiological and laboratory) were normal, suggesting psychosomatic etiology. The characteristics of the headache correspond to a nosologic entity known as tension-type headache. The aim of this study was to evaluate the psychological characteristics of these children and their families, especially the profile of the mothers. The psychological assessment, consecutively applied, comprised: Eysenck Personality Questionnaire (EPQ), Emotions Profile Index (EPI), General Anxiety State (GAS) and Human Values Rank (HVR). The mothers were examined by Family Inventory Life Events (FILE) and Minnesota Multiphasic Personality Inventory (MMPI) and also checked with the Child Behavior Check List (CBCL). The results obtained showed a non-negligible level of actual anxiety in all the children, who were mostly the first-born and lived in families with accentuated stress. The emotional profile of the children was characterized by impulsiveness, a feeling of fear, moderate aggression, but still with a great level of acceptability. The EPQ confirmed their extroversion, moderate neurotic manifestations and a need for social acceptance. These results suggest that in preadolescents emotional stress, combined with a "model" for somatization, could provoke specific involuntary contraction of the head and neck muscles causing local ischaemia, which may be the pathophysiologic cause of a tension-type headache. The therapy comprised EDR and EMG biofeedback, applied once per week, of 50-minute duration. The results obtained after 20 sessions are very satisfactory. In addition, some response-measures involving a change and adjustment of family relations and school environment are recommended. Key words: headache, children, biofeedback, psychophysiology.